KEKUATAN SURAT KETERANGAN HASIL DVI DAN POST-MORTHEM SEBAGAI ALAT BUKTI KORBAN KEBAKARAN YANG MENGAKIBATKAN MENINGGAL DUNIA DIKAITKAN DENGAN PASAL 184 AYAT 3 KUHPIDANA - Kholik, Saeful; Hartawan, Joko (Universitas Wiralodra, 2019)
One of the tasks that have to be done in forensic laboratory is the identification of fire victims with physical forms that are no longer recognizable. However, they still could be identified with the help of certificate from DVI (Disaster Victim Identification) and Post Mortem. One of the problems arise is that the family of the victims have no confidence that the victims identified are their family member. Based on the background of the study above, the researcher intended to conduct a study with the title of ’KEKUATAN SURAT KETERANGAN HASIL DVI DAN POST-MORTHEM SEBAGAI ALAT BUKTI KORBAN KEBAKARAN YANG MENGAKIBATKAN MENINGGAL DUNIA DIKAITKAN DENGAN PASAL 184 AYAT 3 KUHPIDANA’’. According to the tittle above, the identification of the problems are: How is the strength of the proof from the forensic laboratory evidence regarding the fire victims in association with Article 184 Section 3 of the constitution about witnesses? How is the strength of a DVI certificate, Post Mortem, and Anti Mortem in positive rules of Indonesia? This research is a normative juridical legal research. It is a study of laws and regulations in terms of the hierarchy of legislation. Article 133 Section (1) of the Criminal Procedure Code authorizes an investigator to submit a request for information to a judicial medical expert if the investigation involves a victim of injury, poisoning, or death. The expert statement request was made in writing form. It becomes the basis that the power of the DVI, Post Mortem, and Ante Mortem letters is very strong based on Article 133 Section 1 of the Criminal Procedure Code. The letter to be examined is the evidence made by the forensic laboratory. According to Article 187 Letter c of the Constitution Number 8 of 1981 concerning the Criminal Procedure Code states that: